On the accentuation history of Lithuanian denominal verbs in -(i)au-ti - Lukšaitė-Ramonienė, Sandra; Rinkevičius, Vytautas (Baltistica, 2025)
This article examines the accentuation history of Lithuanian denominal verbs in -(i)au-ti. In modern Lithuanian, these verbs typically have suffixal stress, and the few derivatives with root stress are generally formed from nouns of accentual paradigm 1 (e.g., pókštauti ← pókštas, a. p. 1). This situation can be interpreted as a result of Saussure’s Law. An analysis of the relationship between all non-suffix-stressed verbs attested in the Dictionary of the Lithuanian Language (LKŽ) and the accentuation of their base words shows that the vast majority of such verbs are derived from a. p. 1 nouns (e.g., úogauti ← úoga, a. p. 1), and therefore preserve an accentual state inherited from the period before or immediately after the onset of Saussure’s Law. The accentuation of some derivatives with stative meanings and unexpected root stress together with acute metatony (e.g., mérgauti ← mer̃gą) may have been influenced by iteratives of similar semantics. The latter are characterized by root stress and acute metatony inherited from Proto-Baltic (e.g., válkioti ← vel̃ka, cf. Latvian val̃kât ← vȩ̀lk). A small set of verbs derived from color adjectives exhibits circumflex metatony (e.g., juõdauti ← júodas), which appears to have developed under the influence of accent patterns found in analogous -(i)uo-ti derivatives. Other rare instances of non-acute root stress in LKŽ are typically either recent derivatives from Slavic loanwords (e.g., triū̃bauti), possible transcription uncertainties (e.g., beñdrauti), or forms in which the root tone appears to be semantically motivated (e.g., pė̃dauti) or influenced by other factors.